2017
DOI: 10.1007/s12306-017-0474-z
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty for massive irreparable rotator cuff tears and cuff tear arthropathy: a systematic review

Abstract: RSA restores pain-free ROM and improves function of the shoulder in patients with MIRCT or CTA. However, complications occur in a high percentage of patients. The lack of level I studies limits the real understanding of the potentials and limitations of RSA for the management of MIRCT and CTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
75
5
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 53 publications
11
75
5
9
Order By: Relevance
“…Total RSA has recently emerged as an option in the treatment of irreparable MRCTs. 16,17,19 Ernstbrunner et al 16 reported on long-term outcomes after RSA for irreparable MRCTs in 20 patients younger than 60 years. The Constant score improved from 24 to 59, and the SSV increased from 20% to 71%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Total RSA has recently emerged as an option in the treatment of irreparable MRCTs. 16,17,19 Ernstbrunner et al 16 reported on long-term outcomes after RSA for irreparable MRCTs in 20 patients younger than 60 years. The Constant score improved from 24 to 59, and the SSV increased from 20% to 71%.…”
Section: Discussionmentioning
confidence: 99%
“…Petrillo et al 17 reported on outcomes and complications of RSA in 396 patients with an average age of 71.9 years. After surgery, all clinical scores improved in a statistically significant fashion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,21,26 Reverse total shoulder arthroplasty (RSA) has been reported to be the most widely used and effective treatment for patients with mRCT and CTA. 1,3,11,28,34,38 Various biomechanical and clinical studies have demonstrated the advantages of RSA, including the restoration of active forward flexion (aFF) (ie, pseudoparalysis) by increasing anterior and posterior deltoid muscle fiber recruitment and the leverarm function of the deltoid muscle. 2,6,17 Young et al 39 reported that although patients with cuff deficiency who underwent the implantation of an SMR reverse prosthesis (Systema Multiplana Randelli, Lima-LTO, Italy) showed satisfactory forward flexion, none could reach their ipsilateral buttock with their hands.…”
mentioning
confidence: 99%
“…[13][14][15] When there is considerable glenohumeral joint arthropathy, treatment options shift to osseous procedures including glenohumeral joint arthrodesis and, recently, reverse shoulder arthroplasty (RSA). 16 Bridging techniques have been described that improve the biomechanical environment of the repair, with many bridging grafts being used, including long head of the biceps tendon autograft, 17 fascia lata autograft or allograft, 18 and dermal patch allograft, 19 as well as synthetic materials such as poly-L-lactic acid. 20 The purpose of this article was to describe our preferred surgical approach for the reconstruction of a massive irreparable rotator cuff tear using a fascia lata patch autograft.…”
mentioning
confidence: 99%